2013
DOI: 10.1111/eth.12068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microhabitat‐Dependent Predation Risk on Vigilance during Intermittent Locomotion in Psammodromus algirus Lizards

Abstract: Animals should be able to adjust their behavior by tracking changes in predation risk level continuously. Many animals show a pattern of intermittent locomotion with short pauses that may increase detection and vigilance of predators. These locomotor patterns may depend on the microhabitat structure, which affect predation risk levels. We examined in detail in the laboratory the characteristics of spontaneous locomotion, scanning behavior, and the escape performance of Psammodromus algirus lizards moving in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…We postulated that the reduction in habitat structural complexity on ski runs could potentially increase rates of predation on reptiles because individuals basking on, or dispersing across, these areas are more visible to predators. Several studies suggested that rates of predation increase for a suite of different taxa as habitat structure is removed (see Irlandi ; Babbitt & Tanner ; Arthur, Pech & Dickman ) and animal behaviour is altered to compensate for this increased predation risk (or perception thereof; Cuadrado, Martin & Lopez ; Lopez & Martin ). Hence, structural complexity plays an important role in providing protection from predators and reducing perceived predation risk, and this could be driving the distributions of reptiles in subalpine ski resorts and adjacent areas.…”
Section: Introductionmentioning
confidence: 99%
“…We postulated that the reduction in habitat structural complexity on ski runs could potentially increase rates of predation on reptiles because individuals basking on, or dispersing across, these areas are more visible to predators. Several studies suggested that rates of predation increase for a suite of different taxa as habitat structure is removed (see Irlandi ; Babbitt & Tanner ; Arthur, Pech & Dickman ) and animal behaviour is altered to compensate for this increased predation risk (or perception thereof; Cuadrado, Martin & Lopez ; Lopez & Martin ). Hence, structural complexity plays an important role in providing protection from predators and reducing perceived predation risk, and this could be driving the distributions of reptiles in subalpine ski resorts and adjacent areas.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, stimulus detection and predator avoidance might explain why hatchling P. hispanicus alternate short periods of locomotor activity with short pauses. There is evidence that speed reduces perception of moving lizards (Avery, ) and short pauses during locomotion increase detection of both predators and prey (O'Brien, Browman & Evans, ; Trouilloud, Delisle & Kramer, ; López & Martín, ). Thus, brief stops during escape could improve predator vigilance and microhabitat perception, and hence allow hatchlings to adjust their speed or change their sprint direction.…”
Section: Discussionmentioning
confidence: 99%
“…Psammodromus algirus displays a number of antipredator strategies. When predation risk is high, it reduces activity, moves more slowly, and increases vigilance time [52][53][54]. When basking, this lizard stays at ground level near shrubs used as shelters [55].…”
Section: Study Speciesmentioning
confidence: 99%